A polarized view of the hot and violent universe - Soffitta Paolo; Bucciantini Niccolo’; Churazov Eugene; Costa Enrico; Dovciak Michal; Feng Hua; Heyl Jeremy; Ingram Adam; Jahoda Keith; Kaaret Philip; Kallman Timothy; Karas Vladimir; et al. (SPRINGER, 2022)
X-ray polarimetry has long been considered the 'holy grail' of X-ray astronomy. Fortunately, after a silence of more than 40 years, the field is now rejuvenating. In fact, an X-ray polarimeter onboard a Cube-sat nano-satellite has been recently successfully operated. IXPE, the Imaging X-ray Polarimetry Explorer, will be launched in 2021 while eXTP, containing a larger version of IXPE, is expected to be launched in 2027. Although at present it is difficult to predict the discoveries that, given their exploratory nature, IXPE and eXTP will obtain, the path for a follow-up mission can already be envisaged. In this paper we describe the scientific goals of such a follow-up mission, and present a medium-size mission profile that can accomplish this task.